Web Based Toxic Waste Management Information System Using Unified Approach Method - Mareanus Lase; Feri Prasetyo; Yuli Yulianti (Jurnal Mantik, 2020)
Computers are equipment that are created to facilitate human needs, when successful in both hardware and software manufacturing, PT. NU is a company engaged in industry and industry, in their daily activities there must be several parts that produce dangerous and toxic drinks (LB3). However, in this activity very little information is obtained at the time of collecting the waste which results in the accumulation of waste in each producing section, so for this B3 waste system requires computerized development in processing waste data. The purpose of this research is a waste management information system to produce fast, precise and accurate web-based data information with an integrated approach method. This research produces a web-based information system that can support business processes, facilitate the management of waste data, computerize recording, and facilitate reporting. By making this information system design is the best solution to solve existing problems, and with the development of a web-based system can support activities and information systems more quickly, so that all activities carried out are better than the previous system.